Career congruence, motivation and job satisfaction based on Holland's Typology Theory among employees at a print-media company in Indonesia - Mediana, Phycilicia Arsyane (2015)
Print-media company in Jakarta Indonesia, is the most profitable media company compared to others media form. This is one of the reasons why print-media Company is very fast growing in Indonesia, especially in Jakarta. Furthermore, magazine is the most popular print-media in Jakarta Indonesia. One of the biggest print-media companies which publishes magazine is Feminagroup. Unfortunately, Feminagroup had several problems with their employees; increased number of dissatisfaction, turn over and demotivation in 2014. This study is to determine career congruence,motivation and job satisfaction based on Holland Typology Theory among employees at a print-media company in Indonesia. In general, there are five objectives in this study. The first objective is to examine the level of career congruence, motivation and job satisfaction among employees at Feminagroup Jakarta Indonesia. The second objective is to examine the relationship between career congruence and motivation among respondents. Followed by the third objective, which is to examine the relationship between career congruence and job satisfaction. The fourth objective is to identify which of the five components of JDI is the most influential toward motivation among respondents and the last objective is to examine the difference in career congruence, motivation and job satisfaction based on gender among the respondents. This study is a quantitative study, combining descriptive and ex-post facto as a research design. There are 247 respondents in this study and all of the respondents are working in Feminagroup Jakarta Indonesia. Furthermore, there are four sections in the questionnaires (section A-D): demographic section followed by Vocational Preferences Inventory (VPI) by Holland, Motivation Assessment Scale (MAS) by Durand and the last section is Job Descriptive Index (JDI) by Smith et al. The descriptive statistics was used to determine the level of the variables while inferential statistics was also used in this study. From the study, it is found that the level of career congruence is moderate, while the level of motivation among employees and the level of job satisfaction are also moderate. The researcher also found that, there is a positive correlation between career congruence and motivation (r=.007) while, there is no significant relationship between career congruence and job satisfaction (r=.151). The results of multiple regression analysis show that, there are only three components of JDI that have influenced the motivation among the employees. The components are co-workers, supervision and salary (Motivation=53.73-.577(co-workers) +.525 (supervisor)- .430(salary)) and the most influential component of JDI is co-workers. The result of mean differences between gender and career congruence shows that males employees (mean=22.61) are more congruent compared to females employees (mean = 13.12), and male employees (mean = 46.22) are also having high motivation compared to females employees (mean = 42.77), while there is no differences between male and female employees in terms of job satisfaction (p=.457). The findings from this study show that there is a relationship between career congruence and motivation, but there is no significant correlation between career congruence and job satisfaction. Moreover, the results also show that there is a significant relationship between career congruence and motivation toward several job satisfaction components. These findings show that, this study is not in line with Holland typology theory, which states that career congruence will lead to employees’ high motivation and high job satisfaction. The research was done in all general department instead of in specific group or department, thus this may influence the discrepancy of the findings with Holland typology theory. There are also several implications and recommendations of this study for further research. It is found that, the more congruent employees have more motivation as compared to incongruent employees. Job satisfaction also influences career congruence among employees in Feminagroup Jakarta Indonesia. However, not all employees are satisfied with their job though they are congruent. Co-workers is also an important component to boost employees’ motivation and according to McClelland the more needs that employees’ are able to get the more high satisfaction that they feel about their job. There are several recommendations in this study. Firstly, the organization is recommended to evaluate their services and management toward employees from time to time. The organization can also recruit potential employees who suit the company profile. Secondly, it is recommended that every individual especially the respondents of this study to find out the congruency between their personality and the work environment through career counseling. Thirdly, career counselor should use the latest available instrument during counseling session. Lastly, future research could benefit by changing or adding more variables, depending on the purpose of the study, and if it were to be carried out again it is suggested that it is carried out on a different population and or a bigger sample size.